EFEKTIVITAS PROGRAM BANTUAN SOSIAL TUNAI BAGI MASYARAKAT MISKIN TERKENA DAMPAK COVID-19 DI DESA MERANGIN KECAMATAN KUOK KABUPATEN KAMPAR - Siti Marlina; Nur Laila Meilani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The Covid-19 pandemic is a worldwide problem. Various impacts have occurred as a result of this pandemic, one of the most visible is the decline in the economic level that has hit various countries including Indonesia, as a result of which many people find it difficult to make ends meet. Therefore, the government has launched various Social Assistance programs to help the community continue to be able to meet their needs during the pandemic, one of which is the Cash Social Assistance program provided by the Ministry of Social Affairs. The purpose of this study was to determine the effectiveness and inhibiting factors as well as supporting cash social assistance programs for the poor affected by Covid-19 in Merangin Village, Kuok District, Kampar Regency. This study used a qualitative approach with a descriptive research type. Data collection techniques using interview techniques, observation and documentation studies. The informant selection technique used a purposive sampling technique with a total of 8 informants. The theory used is the theory of effectiveness. The results of this study indicate that the provision of Cash Social Assistance in Merangin Village has been carried out properly such as on time, proper administration, provision of adequate resources, but there are irregularities caused by social assistance implementers who are less professional so that social assistance programs are not well targeted to families in need, while the inhibiting factors are the community and the attitude of the implementers who are less honest and professional. Keywords: Effectiveness, Program, Cash Social Assistance